Removal of Ammonia on Catfish Processing Wastewater using Horizontal Sub-Surface Flow Constructed Wetland (HSSFCW) - Bekti Marlena; Rustiana Yuliasni; Sartamtomo; Agung Budiarto; Syarifa Arum; Misbachul Moenir; Cholid Syahroni (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2018)
The performance of Horizontal Sub-Surface Flow Constructed Wetland (HSSFCW) to remove high ammonia content in catfish processing wastewater was investigated. A rectangular HSSFCW with 6 m long, 3 m wide ,1 m deep and divided into 3 compartments was used. Gravel beds were used as medium. Canna sp, Heliconia sp., and Papirus sp. were planted with plant density 10 plants per m2. The result showed that removal of ammonia was 67-87%, nitrite was 26-96%, nitrate was 35-99%. Ammonia removal relies on the efficient nitrification that requires sufficient amount of oxygenand organic carbon source to obtain optimum removal.